Unity 5 AI and physics - Lavieri, Edward D., Jr.; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"Unity is a cross-platform game engine developed by Unity Technologies. It is used to develop video games and simulations for computers, consoles, and mobile devices. In this course, you'll learn how to create a combat system and know how to develop your game's AI. Then you'll learn how to script your players as well as your player's health, spawn your character after death, and keep a tab on scores. As well as all of this, you'll learn a little about game physics, which include particle systems and collisions. By the end of this course, you'll be able to create your very own game using unity 5 tool for any mobile, computer, or console device."--Resource description page.
Presenter, Edward Lavieri.
Title from title screen (viewed November 15, 2017).
Date of publication from resource description page.
Keywords: Unity (Electronic resource); Computer games -- Design; Computer games -- Programming; Video games -- Design; Video games -- Programming; Electronic books